2010
DOI: 10.1159/000280810
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy as an Underlying Mediator of Myocardial Infarction with Normal Coronary Arteries

Abstract: Objective: The purpose of the present study was to describe our experience with myocardial infarction with normal coronary arteries (MINCA) with regards to the prevalence, clinical characteristics, possible underlying etiologies (including Takotsubo cardiomyopathy, TCM) and the short- and long-term outcomes associated with this condition. Methods: We retrospectively analyzed the records of 596 consecutive patients presenting with acute myocardial infarction over a 4-year period and identified 24 patients (14 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Other atypical variants include the basal variant (2.2%) affecting basal segments, the focal variant (1.5%) affecting an isolated segment, and rarely a global variant with hypokinesis of all ventricular segments [ 15 , 16 ]. The atypical variants tend to present in younger patients with a lower prevalence of hypertension [ 17 ]. The stressor type itself appears to modify the pattern of LV dysfunction, with more frequent surgical and disease-related stressors in patients with the atypical variants [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other atypical variants include the basal variant (2.2%) affecting basal segments, the focal variant (1.5%) affecting an isolated segment, and rarely a global variant with hypokinesis of all ventricular segments [ 15 , 16 ]. The atypical variants tend to present in younger patients with a lower prevalence of hypertension [ 17 ]. The stressor type itself appears to modify the pattern of LV dysfunction, with more frequent surgical and disease-related stressors in patients with the atypical variants [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the article by Chen et al [1] , who performed a nice retrospective study on patients with myocardial infarction with normal coronaries (MINCA). Takotsubo cardiomyopathy (TCM) is becoming increasingly important and the findings of the authors are in keeping with previous studies, which have shown TCM to be present in about 2% of patients with acute coronary syndrome (ACS) [2,3] .…”
mentioning
confidence: 99%
“…Chen et al [1] and a number of other investigators have used the Mayo Clinic criteria reported by Prasad et al [4] to confirm the diagnosis of TCM. According to these criteria, one of the main requirements to confirm the diagnosis of TCM is the exclusion of obstructive coronary ar-the sole basis of incidental finding of CAD is not justified.…”
mentioning
confidence: 99%